Association between Pregnancy and Cervical Artery Dissection. Issue 3 (13th July 2020) - Salehi Omran, Setareh; Parikh, Neal S.; Poisson, Sharon; Armstrong, Jennifer; Merkler, Alexander E.; Prabhu, Malavika; Navi, Babak B.; Riley, Laura E.; Fink, Matthew E.; Kamel, Hooman
Abstract : Objective: We wanted to determine whether pregnancy is associated with cervical artery dissection. Methods: We performed a case–control study using claims data from all nonfederal emergency departments and acute care hospitals in New York and Florida between 2005 and 2015. Cases were women 12–42 years of age hospitalized with cervical artery dissection, defined using validated diagnosis codes for carotid/vertebral artery dissection. Controls were women 12–42 years of age with a primary diagnosis of renal colic. Cases and controls were matched 1:1 on age, race, insurance, income, state, and visit year. The exposure variable was pregnancy, defined as labor and delivery within 90 days before or 6 months after the index visit. Logistic regression was used to compare the odds of pregnancy between cases and controls. We performed a secondary cohort‐crossover study comparing the risk of cervical artery dissection during pregnancy versus the same time period 1 year later. Results: Pregnancy was twice as common among 826 women with cervical artery dissection compared with the 826 matched controls with renal colic (odds ratio, 2.5; 95% confidence interval [CI], 1.3–4.7). In our secondary analysis, pregnancy was associated with a higher risk of cervical artery dissection (incidence rate ratio [IRR], 2.2; 95% CI, 1.3–3.5), with the heightened risk limited to the postpartum period (IRR, 5.5; 95% CI, 2.6–11.7). Interpretation: Pregnancy, specifically the postpartum period, was associated with hospitalization for cervical artery dissection. Although these findings might in part reflect ascertainment bias, our results suggest that arterial dissection is one mechanism by which pregnancy can lead to stroke. ANN NEUROL 2020;88:596–602